Assessing and Ensuring a Comprehensive System of Services for Children With Special Health Care Needs: A Public Health Approach - Strickland, Bonnie B. (American Public Health Association, 2011)
The US Department of Health and Human Services called for comprehensive systems of services for children with special health care needs in its Healthy People 2000 and 2010 health care objectives for the nation. We report on the proportion of children with special health care needs receiving care in high-quality systems of services measured by attainment of 6 essential system elements, or quality indicators, generated from a survey of 40 723 families of children with special health care needs in 2005 to 2006. Only 17.7% of children with special health care needs received services in a high-quality service system that met all 6 quality indicators in 2005–2006. Therefore, much more work lies ahead to meet the national Healthy People objective for these children.